Application of self-assembled morphology as microreactors - Lam, Yeng Ming. (2009)
Self-assembly of block copolymers (BCPs) have recently received much attention not only thanks to the scale of the microdomains (tens of nanometers), their various chemical and physical properties (e.g. differential etching rates) but also due to the convenient size and shape tenability of microdomains afforded by simply changing their molecular weights and compositions. Modified block copolymer has proved be a more promising way in preparing nanoparticles.